(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
In March 2020, the World Health Organization declared COVID-19 a global pandemic, which was followed by countries closing their borders partially or completely. The global sector most affected was the tourism and travel sector, as a result of the sensitivity of this sector to crises in general, including health. In addition, the standstill of travel and the closure of airports had a significant impact on the stagnation of this sector due to the vital role of aviation in the travel sector. The Organization for Trade and Development (UNCTAD) estimated that the standstill of international tourism will cost the global economy between 1.2 trillion and 3.3 trillion, and this was estimated within three scenarios, as the organization called it. And the global economy lost 62 million direct jobs, in addition to millions of indirect jobs and big loss in the gross domestic product. This study examined this impact of the Covid epidemic on tourism on a group of tourist countries, and the impact on different sectors as a result of the backward and forward links between tourism and these sectors. The study then dealt with the countries’ efforts to stop these losses and at least mitigate them by developing plans for recovery in the short and medium term to save this sector.